2015
DOI: 10.1089/aid.2013.0211
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSelection of HIV-1 CRF08_BC Variants Resistant to Reverse Transcriptase Inhibitors

Abstract: Human immunodeficiency virus type 1 (HIV-1) circulating recombinant form 08_BC (CRF08_BC), carrying the recombinant reverse transcriptase (RT) gene from subtypes B and C, has recently become highly prevalent in Southern China. As the number of patients increases, it is important to characterize the drug resistance mutations of CRF08_BC, especially against widely used antiretrovirals. In this study, clinically isolated virus (2007CNGX-HK), confirmed to be CRF08_BC with its sequence deposited in GenBank (KF31264… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In the previous study, 14 increasing NVP pressure. The results suggested that these two mutations conferred moderate-to-high-level resistance to NVP in combination with other mutations.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In the previous study, 14 increasing NVP pressure. The results suggested that these two mutations conferred moderate-to-high-level resistance to NVP in combination with other mutations.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, we also assessed the drug susceptibility to NNRTIs of Y188C and found that Y188C conferred a high-level resistance to NVP and a moderate-level resistance to EFV, which was consistent with previous reports from our and others' studies. [37][38][39] Modeling study showed that a hydrogen bond was formed between L228 and Y188 in WT RT. When only a single mutation L228I emerged, it would not affect this hydrogen RCs of these variants were tested by a single-cycle cell culture assay (i).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations